THE PARADIGM OF MERDEKA BELAJAR AND THE TEACHERS' DIGITAL COMPETENCE IN ERA 4.0 - Wijanarko, Heru (International Journal Multidisciplinary (IJMI), 2024)
Education has undergone a significant transformation along with the development of technology. The technological development of Era 4.0 marks a change in the educational landscape, giving rise to the concept of "Merdeka Belajar" as an approach that allows students to organise their own learning. In addition, the role of teachers is becoming increasingly important in this context, on the one hand teachers need a deep understanding of the competencies needed in this digital era. In the technological development of the 4.0 era, teachers are not only required to have high digital competence as an inspirational model for students. Teacher competence in Era 4.0 lies not only in technological proficiency, but also in understanding individual student differences and facilitating learning that accommodates diversity itself. This is apparently what initiated the independent learning approach in the technological development of Era 4.0. Due to continuous changes in the education paradigm, it requires in-depth reflection on how Merdeka Belajar can be applied and how teachers can develop relevant competencies. This paper aims to comprehensively explore the concept of Merdeka Belajar and the dynamics of teacher competence in Era 4.0 by basing it on the latest research.